LINGUISTIC RESEARCH ON SPEECH ONTOGENESIS (Scientific journal of the Fergana State University, 2026)
The main aim of this article is to investigate the linguistic aspects of speech ontogenesis. The process of speech formation in humans is closely connected with biological, psychological, and social factors. Studying it helps to reveal the regularities of child language development and to define the relationship between language and thinking. The study employs descriptive-comparative, linguo-cognitive, and psycholinguistic methods of analysis. In addition, observation data from children’s speech are used for practical analysis. These methods make it possible to systematically identify the stages of speech activity formation. The analysis has shown that during the ontogenesis of speech, children consistently acquire phonetic, lexical, and grammatical levels. The gradual complication of linguistic means is closely related to the expansion of communicative interaction and the development of cognitive activity. A linguistic study of speech ontogenesis has both theoretical and practical significance. Analyzing this process not only clarifies the mechanisms of language development but also provides effective approaches for forming children’s speech skills in educational practice.